Task analysis : - Watson, Diane E. (AOTA, 1997)
The first part of the book provides basic task analysis instruction and the second part provides applications across the lifespan. The case studies and follow-up exercises are excellent. You really feel like you know your "patient" from the readings. Students that are accustomed to read-and-repeat are going to be challenged in reasoning.